Spectrophotometric Determination of Metoclopramide- HCL in the Standard Raw and it Compared with Pharmaceuticals (Journal of Pharmaceutical Negative Results, 2021)
This research has been based on the development of a fast, simple, sensitive, highly selective and accurate way for spectrophotometricestimation of metoclopramide hydrochloride (MCP HCl) drug in various pharmaceutical preparations. The method spectrophotometricdepends on the diazotization of the primary amino group (MCP-HCl) with hydrochloric acid and (NaNO2) solution, also by interaction witha drug considered as a coupling agent is Phenylephrine hydrochloride (PH-HCl) in an alkaline medium. After completing the reaction, theorange color is formed, evidence of forming a stable azo dye for three hours and has a wavelength of 452 nm. Beers’ law was applied in therange concentration of 1-10 mg/L, Correlation coefficient (r2=0.9995). Factors affecting absorbance and color stability were studied likeEffect of sodium nitrite volume, Study of kind and acid concentration, Effect of Phenylephrine hydrochloride volume reagent: the optimumtemperature was 25°C, the reaction time was 5 min., and the volume of Phenylephrine hydrochloride (PH-HCl) reagent was 1ml. The limit ofdetection (LOD) 1.21 x 10-2, the limit of quantification (LOQ) 4.063x10-2. Recoveries range 96.1%-104.1%. The way has been successfullyuseful to analyze the compound (MCP-HCl) in its pharmaceutical preparations (tablets, syrup).